Preparação de carvão ativado a partir de casca de amendoim para uso como adsorvente na remoção de poluentes orgânicos em soluções aquosas - Georgin, Jordana (2016)
The contamination of water bodies by dye containing effluents is harmful for the environment and human health. In this way, several techniques have been used to remove dyes from colored effluents. Adsorption stands out, due its low-cost, low energy requirements, use of low-cost adsorbents, ease of implementation and operation and high efficiency. In this work, peanut shells were used as adsorbents and as precursors to obtain activated carbon. These materials were characterized and used to remove DB38 (Direct Black 38) and RR141 (Reactive Red 141) dyes from aqueous media. It was found that the best adsorbents to remove both dyes were in the following order: microwave/pyrolyzed activated carbon from peanut shells>pyrolyzed activated carbon from peanut shells>peanut shells. This result demonstrated that the microwave irradiation followed by pyrolysis is an alternative way to produce a material with good adsorbent characteristics. The adsorption was favored at pH of 2.5. For both dyes, the kinetic was successfully represented by the pseudo second order model and the equilibrium, represented by the Langmuir model. Desorption and reuse was possible maintaining the same adsorption capacity. In brief, these results revealed that peanut shells are a good precursor to obtain a suitable adsorbent material able to remove dyes from aqueous media.